KEWENANGAN MAHKAMAH KONSTITUSI DALAM PENYELESAIAN SENGKETA PEMILU BERDASARKAN HUKUM POSITIF INDONESIA - Fakhlevi, Raja Ferza; Asnawi, Eddy; Kadaryanto, Bagio (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The Constitutional Court provides the widest possible opportunity for the entire community to make optimal use of the existence of the Constitutional Court in the constitutional system. By developing the procedural process in a better direction, which is carried out in a modern, fast, simple and cost-free manner, which is related to trial management, case time and simple procedures in submitting and examining applications. The purpose of this research is to analyze the authority of the Constitutional Court in resolving election disputes based on Indonesian positive law. The method used is normative legal research. Based on the research results, it is known that the Authority of the Constitutional Court in Resolving Election Disputes Based on Indonesian Positive Law is that the General Election Commission is one of the state institutions that is given the authority by law to form its own legal products of statutory regulations, namely in the form of General Election Commission Regulations. Seeing that its position is actually outside the hierarchy of statutory regulations, the position of the General Election Commission Regulation in the legal system in Indonesia automatically becomes very abstract because the material content contained in the General Election Commission Regulation does not fully apply to all parties and the legal force of the Commission Regulation General Elections only apply in the implementation of Regional Head Elections and General Elections so that their binding force cannot apply fully in general. The basic reasons that became the reference for why the authority for regional election disputes was finally transferred from the Supreme Court to the Constitutional Court were, firstly, seeing that the regional elections were basically included as an election regime, so that disputes over election results had to be resolved at the Constitutional Court in accordance with the 1945 Constitution. Second, this was contained in the 1945 Constitution Article 24 C paragraph 1 states that the Constitutional Court is an institution that has the authority to adjudicate at the first and last level whose decisions are final.